Comedy and feminist interpretation of the hebrew Bible: a subversive collaboration - Jackson, Melissa A (Oxford theological monographs, 2012)
Exploring the Hebrew Bible for evidence of comedy, this volume further asks how reading the Hebrew Bible through a comic 'lens' might positively inform feminist interpretation. The exploration is conducted with a number of Hebrew Bible narratives, all of which prominently involve female characters.